A Case of Off-label Sodium Oxybate in an 11-Year-Old with Narcolepsy - Miskoff, Jeffrey A (Cureus, 2019)
Narcolepsy is a rare chronic condition which affects sleep architecture. It may manifest in childhood or adolescence by causing excessive daytime sleepiness, sleep attacks, and hallucinations. Research suggests that there is a significant delay in diagnosis with the mean age being 10 to 15 years from onset of symptoms. Although narcolepsy is predominantly associated with loss of hypocretin (orexin), the role of genetics is complementary to the diagnosis. In addition, clinical manifestations of symptoms vary in presentation and severity from case to case. Therefore, this report provides an opportunity to review pediatric narcolepsy including the diagnostic workup and clinical response to sodium oxybate. This particular case describes an 11-year-old boy meeting the clinical and diagnostic criteria for narcolepsy. Clinically, the patient had a very positive response to treatment with sodium oxybate, which at the time of initiating therapy was off-label for patients under the age of 18.